Region Augmentation and Development Distribution in Lampung Province - Ambya Ambya (Politeknik Negeri Lampung, 2011)
Regency augmentation performs interesting phenomenon approximating the new autonomous region in Lampung Province. There had been 10 the new autonomous regions since 1991 until 2008. The regency augmentation has been presenting the opportunity and new hope for the autonomous region to arrange its own region dialed with welfare escalation and enlargement distribution. Even though, Regency financing still depend on centralization transfer called general fund allocation. This paper purposes to analyze the regional inequality between regency and the regency dependency on fiscal toward general fund allocation in Lampung Province. This study did in June until October 2010 with the purposive sampling regency included West Lampung, Tanggamus, Tulang Bawang, East Lampung, Way Kanan and Metro regency. Time series data analysis with Williamson inequality index and finance dependency with share portion. Based on the analysis, the Williamson index on region inequality between the new autonomous region and the elderly region performed on lower condition. It is indicating that regency augmentation has been succeeding in creating the development distribution in Lampung Province. Fiscal dependency on general fund allocation accessible is more than 60% until 80% on income region. In general, this means that the new autonomous region still depend on general fund allocation significantly, except Tanggamus regency. Key words: augmentation, the regional inequality, general fund allocation